-13-2p=-7p-8p

Simple and best practice solution for -13-2p=-7p-8p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13-2p=-7p-8p equation:


Simplifying
-13 + -2p = -7p + -8p

Combine like terms: -7p + -8p = -15p
-13 + -2p = -15p

Solving
-13 + -2p = -15p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '15p' to each side of the equation.
-13 + -2p + 15p = -15p + 15p

Combine like terms: -2p + 15p = 13p
-13 + 13p = -15p + 15p

Combine like terms: -15p + 15p = 0
-13 + 13p = 0

Add '13' to each side of the equation.
-13 + 13 + 13p = 0 + 13

Combine like terms: -13 + 13 = 0
0 + 13p = 0 + 13
13p = 0 + 13

Combine like terms: 0 + 13 = 13
13p = 13

Divide each side by '13'.
p = 1

Simplifying
p = 1

See similar equations:

| 4+4r=22 | | -10(-p-8)-2=268 | | 4x-9=3.5x+9 | | 9x+0.8=9.8 | | -5p+5p=-12+6p | | -10x+x-1=7x-5 | | 1=10x-4 | | 5p+5p=-12+6p | | x^2+4x+y^2-10y=16 | | 2e=1000 | | 3(2x-4)=8x-12 | | 10-(1+3b)=-20 | | -26-16x=10-19x | | 3(-1.3)+9=5 | | 427.5=t^2+55t | | 2-2a=a-13 | | 125=-9d+8 | | 6+5=-37 | | 2.9n=11.7 | | 13=6r-5 | | 1-(1+3b)=-20 | | 53.00=10.5(2)+4d | | 4+4x+25-5x=23 | | -2v-(-1-2v)=9-2v | | 8x-12=6x-12 | | 13=k+17 | | 5a+11=46 | | 17x^2+19x=0 | | D=r+rst | | 2v+6=-2+6v | | 28(3.25)-7+12y+30=180 | | 3x+21x-1=6(4x+4) |

Equations solver categories